Evolutionary optimization of Haferman carpet fractal patterned antenna array. Issue 8 (11th May 2015) - Ghatak, Rowdra; Karmakar, Anirban; Poddar, Dipak R.
Abstract This article investigates radiation characteristics of a new type of fractal shaped antenna array based on Haferman carpet geometry. An iterative feed matrix eases the complexity of array factor calculation that makes the array factor suitable for the application of any evolutionary optimization techniques. It is seen that Haferman carpet array produces peak side lobe level (PSLL) better than Sierpinski carpet that produces −10 dB PSLL at every stage of growth. Optimization techniques have been applied for array element reduction and PSLL minimization at different stages of growth. Here, PSLL is minimized by turning off array elements and also by varying inter element spacing between the array elements. The optimized version of Haferman carpet array produces better characteristics (49.38% thinning with −20.5 dB PSLL for stage‐2, 46.3% thinning with −22 dB PSLL for stage‐3 and 42.3% thinning with −21dB PSLL for stage‐4) than its original counterpart in terms of reduced element count and PSLL. Numerical results for obtaining optimized array performance exploit both DE as well as PSO. A comparative study on the performance is also presented. As a whole, Haferman carpet is seen to be more effective approach than Sierpinski carpet in fractal antenna paradigm. © 2015 Wiley Periodicals, Inc. Int J RF and Microwave CAE 25:719–729, 2015.